PELATIHAN KETRAMPILAN PUBLIC SPEAKING DALAM MENINGKATKAN KUALITAS MENJADI MASTER OF CEREMONY BAGI IBU PKK DI KECAMATAN PANTAI CERMIN - Budiman Purba; Afriadi Amin; Muya Syaroh Iwanda Lubis; Amru yasir (MAJU : Indonesian Journal of Community Empowerment, 2025)
Public speaking is not just about talking, it's a soft skill that anyone can learn. Public speaking, whether in the workplace, recreation, social, educational or organizational context, requires special skills. Problems that many people experience when speaking in front of an audience include lack of confidence, nervousness, memory loss, stuttering, not understanding the content of the speech, and not being able to improvise well, which can eventually become monotonous. cannot control the audience, and so on. The beginning of becoming an MC is with the intention and willingness to always try to speak in front of the public. The implementation method in this training activity is training, education, simulation and demonstration until evaluation. The result obtained, many mothers are interested and interested in becoming MC in every activity, and continue to try in training and when there is a simulation or demonstration..